Map showing the location of the Greely Party : the route of their retreat, and the most northerly points reached (Struthers, Servoss & Co., 1884)
Shows southern coast of Lincoln Sea and south toward Kane Basin. Relief shown by hachures and spot heights. Depths shown by soundings. Grayscale